Overview of Knowledge Level of Trimester III Pregnant Women Against the Dangers of Using High Heels in BPM Hanimar Tangah Sawah Bukittinggi (JURNAL IBU DAN ANAK, 2023)
Pregnancy is a gift beyond measure for married couples. During pregnancy a lot of things that must be considered the mother from maternal nutrition. User of high heels on inu pregnancy can cause stretching of the muscles in the area pinggang. The purpose of this study is to describe the knowledge of pregnant women to the dangers of the use of high heels. The negative effect of high heels also includes the pelvis up so abnormal shape and size butt getting bigger. Pelvis cavity disorders (pelvis) in pregnant women can cause difficult childbirth. This type of research is descriptive. Population around the third trimester pregnant women is 24 people. Collecting data using questionnaires. The sampling technique is non-random sampling with accidental sampling. Data analysis technique with univariate analysis. Results of research conducted in BPM Hanimar Tangah Sawah Bukittinggi found the level of knowledge of the third trimester pregnant women are low, namely 18 respondents (75,0%). So the conclution is the level of knowledge of pregnant women in the third trimester in BPM H knowledge low of 18 respondents (75,0%). It is suggested to midwife Hanimar to provide health knowledge about the dangers of the use of high heels.